the Effectiveness Of Birthball On Labor Pain In The 1st Active Phase - Asni Fauziyah, Gianti; Ulfah, Kurniati; Pascawati, Riana (Jurnal Kesehatan Siliwangi, 2024)
Labor pain during the first stage is severe pain that is felt by the mother in labor for a longer time. Based on the Indonesian Hospital Association Data Center, it was explained that 16% of mothers in Indonesia experienced birth complications and 21% stated that the labor they experienced was a painful labor because they felt excruciating pain, while 63% did not receive information about labor complications. Several types of management for dealing with pain using non-pharmacological methods, which are preferred by birth mothers to deal with pain, are the distraction method with a birth ball. The method used is a case study of mothers giving birth. The aim of this case study is that students are able to apply and find out the effectiveness of birth balls as pain relief for mothers giving birth during the first active phase. The results of the case study showed that the birth ball was an effective way to reduce pain in the first stage of the active phase of labor.